2012
DOI: 10.1002/wmts.63
|View full text |Cite
|
Sign up to set email alerts
|

The cellular life of pannexins

Abstract: The mammalian pannexin family of channel-forming proteins consisting of Panx1, Panx2, and Panx3 has received considerable attention in the last 10 years given their newly discovered physiological roles in development and disease. Pannexins exhibit diverse subcellular profiles indicating that they may serve distinct roles in cells and tissues of different origin. This complexity in cellular residencies may be rooted in the fact that pannexin genes consist of multiple exons that have led to the identification of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 57 publications
0
16
0
Order By: Relevance
“…15 Panx1 has been detected preferentially in the surface membrane but has also been found in intracellular compartments in rat atrial and ventricular primary cardiomyocytes. 24,25 Unfortunately, our results do not allow us to identify if this greater expression occurs in the plasma membrane or at intracellular compartments of the cells.…”
Section: Discussionmentioning
confidence: 76%
“…15 Panx1 has been detected preferentially in the surface membrane but has also been found in intracellular compartments in rat atrial and ventricular primary cardiomyocytes. 24,25 Unfortunately, our results do not allow us to identify if this greater expression occurs in the plasma membrane or at intracellular compartments of the cells.…”
Section: Discussionmentioning
confidence: 76%
“…A previous study in murine postnatal hippocampal neural progenitor cells (NPC)s [ 17 ] showed that treatment with glycosidases had no effect on endogenous Panx2 electrophoretic mobility, suggesting that they were un-glycosylated. That study relied on antibody detection of endogenous Panx2, and the protein bands identified were of lower molecular weight than the predicted full-length Panx2 used in this study (677 aa, [ 39 ]). Further studies are needed to determine first, if the expression of certain un-glycosylated endogenous isoforms of Panx2 is cell-type specific, and second, whether glycosylation has measurable effects on the Panx2 cellular function.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, our understanding of the role of these two isoforms in cancer is limited. Panx3 plays a role in proliferation and differentiation of cells in skin, cartilage and bone [ 182 ], so we predict that we will soon learn more about a potential role for Panx3 in skin cancer and osteosarcomas. Panx2 has been proposed to play an important role as a tumour suppressor in brain tumours and hepatocellular carcinomas (Table 2 ).…”
Section: Pannexin 2 As a Tumour Suppressormentioning
confidence: 99%